The lived experience of self-injury stigma and its psychosocial impact: a thematic analysis - Stephen P. Lewis; Joanna Collaton; Riley L. Pugh; Nancy L. Heath; Rob Whitley (BMC Psychology)
Abstract Background Non-suicidal self-injury (NSSI) represents a prevalent and significant mental health difficulty experienced by young adults. Few efforts have explored lived experience perspectives concerning the impact of NSSI stigma, despite long-standing recognition that NSSI is highly stigmatised and recent calls for more research in this area. New insights would be fruitful in identifying which manifestations of stigma are most germane to people who engage in NSSI and what stigma-related supports they may need. Accordingly, the present study sought to understand lived experience perspectives regarding the impact of NSSI stigma. Method A total of 97 young adults with a mean age of 19.32 years (standard deviation [SD] = 2.17) participated in the present study. Participants completed an online survey, including open-ended questions asking about how they have been impacted by NSSI stigma and how they believe people are generally impacted by such stigma. Reflexive thematic analysis was used to analyse text-based responses. Results Our analysis yielded four themes, namely: Shamed into Silence; Unspoken but Sensed Stigma; Anticipation and Avoidance of Stigma, Enduring Shadow of Stigma. These implicate internal forms of stigma - namely, self and anticipated stigma. Collectively, such stigma fomented a significant and often ongoing psychosocial burden involving shame and disclosure reluctance. Participants also perceived external stigma from others, highlighting both verbal and non-verbal considerations therein. Conclusion The current findings highlight several psychosocial consequences of NSSI stigma for individuals with lived experience. In this way, this study adds to a growing body of work illustrating the value of lived experience perspectives in NSSI research and has important implications for research, anti-stigma work, and clinical practice.